Role of clinical and paraclinical manifestations of methanol poisoning in outcome prediction - Shahin Shadnia; Mojgan Rahimi; Kambiz Soltaninejad; Amir Nilli (Journal of Research in Medical Sciences, 2013)
Background: Methanol poisoning is one of the most important poisoning due to drinking of illegal and non-standard alcoholic beverage in some countries. Relatively limited studies have been carried out to identify the prognostic factors in methanol poisoning. Materials and Methods: We performed a retrospective study on acute methanol-intoxicated patients, which were admitted on the Loghman Hakim Hospital Poison Center (Tehran, Iran) over a 24-month period. The demographic data, clinical manifestations and paraclinical findings, therapeutic interventions and outcome (survivors with or without complications and non-survivors) were extracted. Results: We evaluated 30 patients with methanol poisoning during 2 years. All of the patients were male; with the median age of 25.5 years. Visual disturbances, respiratory manifestations, and loss of consciousness were the most common clinical manifestations on admission time. The results of paraclinical manifestations on admission time were as following: The median of blood methanol level was 20 mg/dL. The median of pH, PaCO 2 and HCO 3 was 7.15, 22.35 mmHg and 7.2 mEq/L, respectively. Hyperglycemia was observed in 70% of the patients and the median of blood glucose was 184.5 mg/dL. In fourteen of the patients hemodialysis was performed. Median duration of hospitalization was 48 h. Nine of the patients died. There was a significant difference between survivors and non-survivors with regard to coma, blood methanol level, and PaCO 2 and blood glucose. Furthermore, we did not observe a significant difference between these two groups regarding to pH, HCO 3 level, and time interval between alcohol ingestion to hospital admission and beginning of hemodialysis. Conclusion: Regarding the results of this study, it can be suggested that coma, PaCO 2 and hyperglycemia on admission time could be used as strong predictors of poor outcome.